Implementasi Relai Low Impedance Pada Gardu Induk 150 kV Lengkong Lama - Hermawan, Ahmad; Harijanto, Priya Surya; Wiguno, Fadhil; Hermawan, Satria Luthfi (Elposys: Jurnal Sistem Kelistrikan, 2025)
The substation played a vital role in the distribution of electrical power from the generator to end users, requiring a reliable protection system to ensure continuity and safety. At the 150 kV Lengkong Substation, the existing busbar protection system used an electromechanical high impedance relai, which lacked the sensitivity, selectivity, and reliability demanded by current operational standards. This research aimed to improve the reliability of the substation’s protection system by replacing the high impedance relai with a digital low impedance numerical relai (GE P746). The method involved direct field observation, data collection, and system testing, including individual relai tests, functional evaluations, and differential current calculations. Tap settings and wiring integration were adjusted to accommodate the new relai's configuration and performance standards issued by PT PLN (Persero) UIT JBB. The findings showed that the new relai functioned well in normal operation, block trip, and block all modes. The differential current (Idiff) calculations at Busbar 1 and Busbar 2 yielded 9.32 A and 28.25 A respectively—both well below the 80 A protection threshold, indicating system stability and correct operation. These results confirmed that the upgraded relai system operated within the safe zone and did not trigger false trips. This study highlighted the necessity of modernizing protection systems across substations and recommended further integration with digital communication protocols such as IEC 61850 to enhance future grid reliability and responsiveness.